2018
DOI: 10.1038/s41386-018-0093-x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced GABAergic cortical inhibition in aging and depression

Abstract: The neurobiology underlying depression in older adults is less extensively evaluated than in younger adults, despite the putative influence of aging on depression neuropathology. Studies using transcranial magnetic stimulation (TMS), a neurophysiological tool capable of probing inhibitory and excitatory cortical neurotransmission, have identified dysfunctional GABAergic inhibitory activity in younger adults with depression. However, GABAergic and glutamatergic cortical neurotransmission have not yet been studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 92 publications
1
33
0
Order By: Relevance
“…Abnormal peripheral serum concentrations of GABA and glutamate, and reduced brain levels of the enzyme glutamic acid decarboxylase (GAD), which is responsible for converting glutamate to GABA, have been found in young adults diagnosed with depression and schizophrenia [77]. Changes in GABAergic neurons and in the concentration of GABA B -R isoforms, have been discovered in post-mortem examination of patients diagnosed with clinical depression, and support the theory of involvement of the GABAergic system in psychiatric disorders [77,92,93].…”
Section: Gaba B Receptor Pathophysiologymentioning
confidence: 85%
“…Abnormal peripheral serum concentrations of GABA and glutamate, and reduced brain levels of the enzyme glutamic acid decarboxylase (GAD), which is responsible for converting glutamate to GABA, have been found in young adults diagnosed with depression and schizophrenia [77]. Changes in GABAergic neurons and in the concentration of GABA B -R isoforms, have been discovered in post-mortem examination of patients diagnosed with clinical depression, and support the theory of involvement of the GABAergic system in psychiatric disorders [77,92,93].…”
Section: Gaba B Receptor Pathophysiologymentioning
confidence: 85%
“…Converging reports on stress‐induced GABA and glutamate dysfunction have shown that the impaired balance of neural excitation and inhibition is a characteristic feature of depression pathophysiology . In addition, novel rapid‐acting agents and allosteric modulators of glutamate or GABA receptor complexes can reset both excitatory and inhibitory neurotransmitter systems . The neurotrophin signaling, MAPK and PI3K‐Akt signaling pathways were closely related to the BDNF/TrkB‐dependent PI3K/Akt/mTOR1 pathway, according to the pathway diagram provided by the KEGG database.…”
Section: Discussionmentioning
confidence: 99%
“…To explore whether any changes in cortical physiology at 12 weeks reflected normalization toward healthy control values, we compared post-treatment TMS measures of LLD patients with baseline TMS measures of older and younger healthy adults previously published by our group (Appendix 1). 10 We also performed subgroup analyses to assess the robustness of the primary findings in subgroups of interest, including females, males, participants with early-onset depression (onset of first depressive episode before age 60), participants with late-onset depression (first onset at age 60 or later), participants previously treated with an adequate antidepressant trial, participants not previously treated with an adequate antidepressant trial, participants whose final venlafaxine dosage was less than 225 mg/d, and participants whose final venlafaxine dosage was 225 mg/d or more 22 , 37 (Appendix 1, Table S1). Similarly, we performed sensitivity analyses to assess the robustness of the primary findings in the absence of potential confounds: left-handed 38 participants or those whose handedness was unknown, participants with concurrent benzodiazepine or zopiclone use, participants taking a low dose of trazodone or another antidepressant at the time of baseline measurements due to cross-titration, or participants with a comorbid anxiety disorder (Appendix 1, Table S2).…”
Section: Methodsmentioning
confidence: 99%
“… 5 For example, TMS studies have provided in vivo evidence of impaired cortical inhibition and plasticity in younger and mid-life adults with depression 6 , 7 and in older healthy adults. 8 10 We have previously shown that similar abnormalities in cortical physiology in patients with early- and late-onset LLD may be influenced by depression- or aging-related changes in these same cortical processes; 10 however, the relative influences of depression versus aging on the pathophysiology of depression in older adults cannot be teased apart in cross-sectional studies.…”
Section: Introductionmentioning
confidence: 99%